Comparison study on secrecy probability of AF-NOMA and AF-OMA networks - Dinh-Thuan Do; Minh-Sang Van Nguyen; Thi-Anh Hoang (Universitas Ahmad Dahlan, 2019)
The strictly positive secrecy capacity (SPSC) performance is examined in a new design of non-orthogonal multiple access (NOMA) considered in this study. This system model employs Amplify-and-Forward (AF) relaying scheme to serve far users. In this scheme, a transmitter sends confidential signal to far users. It can be raised falling performance in the presence of an external eavesdropper in such NOMA system. With regard to orthogonal multiple access (OMA), performance of NOMA system model is compared. In particular, tradeoff the SPSC performance and transmit SNR is examined. In this study, the SPSC is evaluated as the secrecy metric to limit impacts of the practical passive eavesdropper in real scenario. It is confirmed that the secrecy performance of NOMA is significant lower than OMA due to related parameters characterization in NOMA, and it should be controlled by varying related coefficients. As main results, both of NOMA and OMA against to impact of eavesdropper is studied in terms of analytically result and numerically result.